Tropical Free‐Tropospheric Humidity Differences and Their Effect on the Clear‐Sky Radiation Budget in Global Storm‐Resolving Models - Theresa Lang (American Geophysical Union (AGU), 2021)
Abstract Reducing the model spread in free‐tropospheric relative humidity (RH) and its response to warming is a crucial step toward reducing the uncertainty in clear‐sky climate sensitivity, a step that is hoped to be taken with recently developed global storm‐resolving models (GSRMs). In this study we quantify the inter‐model differences in tropical present‐day RH across GSRMs, making use of DYAMOND, a first 40‐day intercomparison. We find that the inter‐model spread in tropical mean free‐tropospheric RH is reduced compared to conventional atmospheric models, except from the tropopause region and the transition to the boundary layer. We estimate the reduction to ∼50%–70% in the upper troposphere and 25%–50% in the mid troposphere. However, the remaining RH differences still result in a spread of 1.2 Wm−2 in tropical mean clear‐sky outgoing longwave radiation (OLR). This spread is mainly caused by RH differences in the lower and mid free troposphere, whereas RH differences in the upper troposphere have a minor impact. By examining model differences in moisture space we identify two regimes with a particularly large contribution to the spread in tropical mean clear‐sky OLR: rather moist regimes at the transition from deep convective to subsidence regimes and very dry subsidence regimes. Particularly for these regimes a better understanding of the processes controlling the RH biases is needed.